Frontloading HIV financing maximises the achievable impact of HIV prevention - Anderson,S; Ghys,PD; Ombam,R; Hallett,TB (Journal of the International AIDS Society, 2018)
Introduction:Due to the nature of funding, national planners and international donors typically balance budgets over short time periods when designing HIV programmes (˜5year funding cycles). We aim to explicitly quantify the cost of shortterm funding arrangements on the success of future HIV prevention programmes.Methods:Using mathematical models of HIV transmission in Kenya, we compare the impact of optimized combination prevention strategies under different constraints on investment over time. Each scenario has the same total budget for the 30year intervention period but the pattern of spending over time is allowed to vary. We look at the impact of programmes with decreasing, increasing or constant spending across 5year funding cycles for a 30year period. Interventions are optimized within each funding cycle such that strategies take a shortterm view of the epidemic. We compare these with two strategies with no spending pattern constraints: one with static intervention choices and another flexible strategy with interventions changed in year ten.Results and Discussion:For the same total 30year budget, greatest impact is achieved if larger initial prevention spending is offset by later treatment savings which leads to accumulating benefits in reduced infections. The impact under funding cycle constraints is determined by the extent to which greater initial spending is permitted. Shortterm funding constraints and funds held back to later years may reduce impact by up to 18% relative to the flexible longterm strategy.Conclusions:Ensuring that funding arrangements are in place to support longterm prevention strategies will make spending most impactful. Greater prevention spending now will bring considerable returns through reductions in new infections, greater population health and reductions in the burden on health services in the future.